Upper Eyelid Nodule - An Unusual Presentation of Ocular Demodicosis - Handa, Sabia; Goyal, Parul; Sharma, Suryaprakash; Bal, Amanjit; Singh, Manpreet; Gupta, Pankaj (Nepalese Journal of Ophthalmology, 2021)
Introduction: Demodex mite is an external parasite which is implicated in various ocular conditions like anterior blepharitis, posterior blepharitis, meibomian gland dysfunction, chalazia and others. Although demodex has been shown to be a causative agent of chalazia, occurrence of a solitary inflammatory nodule due to demodex infestation has not been reported in literature. Case: Our case describes the occurrence of an upper eyelid mass in a 62-year-old female which was found to have an associated demodex infestation. Conclusion: This is the first report of demodex infestation presenting as a nodular eyelid mass. This parasite needs to be considered in the differential diagnosis of eyelid masses as this condition requires specific management.